2010
DOI: 10.1111/j.1471-0528.2009.02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal autonomic response to severe acidaemia during labour

Abstract: The autonomic nervous system of human fetuses at term responds adequately to severe stress during labour. Normalised low and high frequency power of heart-rate variability might be able to discriminate between normal and abnormal fetal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 41 publications
1
59
3
Order By: Relevance
“…LF and HF HRV markers performed better than after their respective normalization by the total power in the 0.04-1.50 Hz band of the RR interval autospectrum. This contrasts with the findings by van Laar et al (14), who did not find significant hypoxia-induced changes in the LF and HF HRV markers but did find significant changes in their normalized counterparts. The different findings might be due to age of the subjects involved (term vs. preterm), which would indicate that domain-based HRV markers for hypoxia are age specific.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…LF and HF HRV markers performed better than after their respective normalization by the total power in the 0.04-1.50 Hz band of the RR interval autospectrum. This contrasts with the findings by van Laar et al (14), who did not find significant hypoxia-induced changes in the LF and HF HRV markers but did find significant changes in their normalized counterparts. The different findings might be due to age of the subjects involved (term vs. preterm), which would indicate that domain-based HRV markers for hypoxia are age specific.…”
Section: Discussioncontrasting
confidence: 57%
“…Depressed temporal HR variability correlates to acidosis, (13) and frequency domain-based normalized LF and HF HRV markers were likewise correlated to acidosis (14). Temporal HRV was calculated as the SD of HRs of 5 min, and this is reflected in sharp transitions at the start and end of UCO (Supplementary Figure S3 online), when HR abruptly changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that fetal heart-rate variability (HRV) is affected by metabolic acidosis during labor [19,20] . HRV is mediated by parasympathetic and sympathetic activities, which involve two arms of the autonomic nervous system (ANS).…”
Section: Introductionmentioning
confidence: 99%
“…With computerized analysis of tracings now available, we can rigorously test hypotheses about EFM patterns, such as the optimal defi nition of reduced variability. Furthermore, it is also possible to separate the different frequency components of heart rate variability corresponding to the clinical concepts of short-and long-term variability [22,38,50,64,69] . Considerable debate remains regarding the best method to measure the various components of variability and what components or ratio of components are the most discriminating of metabolic acidemia in general [22,50,52,64,68] .…”
Section: Three Basic Steps In Clinical Monitoringmentioning
confidence: 99%